Liquid Fuel Combustion in a Burner System: A Short Review - Amirnordin, Shahrin Hisham; Amir Khalid; Jerome Devan Lourdes Christopher Anthony (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Fossil fuels have been the major energy resource of the world. However, the gaseous that produced by combustion of fuel is poisonous and it can lead to health problems for living things. This paper review the main factors which contribute to the combustion of the burner system. The main parameters considered are flame length, flame height, flame area, flame temperature and emission of gases. The first part of this study recaps on the flame characters. The second part discuss the effects of on the flame temperature of the burner system. The final section discusses the emission characteristics on emissions of nitrogen oxide, carbon monoxide, sulphur dioxide and carbon dioxide. The outcome of this paper provides an understanding of the combustion characteristics towards the performance of burner system.